Writing the past, writing the future : time and narrative in gothic and sensation fiction - Albright, Richard S., 1951- (Lehigh University Press, 2009)
This book links popular British fiction from the 1790s through the 1860s to anxieties about time. The cataclysm of the French Revolution, discoveries in geology, biology, and astronomy that greatly expanded the age and size of the universe, and technological developments such as the railway and the telegraph combined to transform the experience of time and dramatize its aporetic nature--time as inarticulable contradiction.